Polar Codes : The Error Correcting Codes in 5G Communication Systems - Tuntiputra, Nut; Sri Rungroj, Gun; Wuttisittikulkij, Lunchakorn; Phakphisut, Watid (Journal of Digital Communications, 2019)
This study presents the details of polar codes which is an experimental research for new type of error correcting codes adopted for the new standard in the 5th Generation of wireless communication systems or 5G. The structure of Polar codes defines by 4 parameters ; is length of codewords; is length of data bits; is a position of frozen bits equal to and is vector that contains binary bit 0 or 1. The encoding of the Polar codes was created by the generator matrix which is the multiply Kronecker product of for times then set a position of forzen bits. Next, the perfomance of Polar codes was estimated on additive white Gaussian noise (AWGN) channel. Decoding the Polar codes was done by changing the signal form AWGN channel to Likelihood Ratio (LR). The bit error rate was also evaluated performances over additive white Gaussian noise (AWGN) channel. The stimulation in which of decoding the structure of Polar codes at 2/3 has bit error performance better that at 1/2 and 1/3, respectively. On the other hand, the sending time for decoding of Polar codes at 2/3 has greater than 1/2 and 2/3, respectively. According to this finding, the performance of bit error rate at 2/3, 1.2 and 2/3 is chronological better. However, the processes for sending the data require more time period.